Effects of alkali stress on antioxidant capacity, lipid metabolism, apoptosis and autophagy of Eriocheir sinensis - Jia Liu; Yihan Kou; Dexuan Kong; Zihao Yan; Zhengyao Guo; Wei Lu; Wenfa Lv; Yuehong Li (Scientific Reports)
Abstract This study investigates the effects of alkali toxicity on Chinese mitten crab (Eriocheir sinensis) exposed to 17.5 mmol/L alkalinity for four weeks. Alkali toxicity resulted in significant physiological responses, notably reducing survival rates. There was a marked increase in MDA content and a decrease in SOD, CAT, and T-AOC levels in the hemolymph. Additionally, there was an elevation of ROS levels in the gills and hepatopancreas, along with Keap1 expression, leading to tissue oxidative damage. Alkalinity exposure induced apoptosis, significantly increasing the mRNA expression of Bax, caspase3, P53, and a notable rise in TUNEL-positive cells. Long-term alkali exposure also reduced hepatopancreas lipid accumulation by promoting CPT1 while inhibiting SREBP, ACC, and CAAT expression. Furthermore, autophagy was considerably influenced by alkali stress, as evidenced by the upregulation of mRNA expression of ATG5, ATG7, LC3a, Beclin1, as well as the protein expression of Beclin1 and parkin. Overall, the findings indicate that alkalinity exposure triggers oxidative stress, lipid metabolic disorder, apoptosis, and autophagy in E. sinensis, providing insights into how E. sinensis adapts to saline-alkali environments and sustainable development in saline-alkali waters.